Pengaruh Gaya Kepemimpinan, Pengawasan, dan Disiplin Kerja Terhadap Kinerja Karyawan PT Palmaris Raya Kebun Batahan Mandailing Natal - Azariah, Azariah; Haryati, Rice; Yuliastanty, Susi (Ekasakti Matua Jurnal Manajemen, 2024)
The purpose of this study was to analyze and determine: 1) Which variable in the salary range of employees of PT Palmaris Raya Kebun Batahan Mandailing Natal is the most dominant factor. 2) Partial analysis of the employment conditions of employees of PT Palmaris Raya Kebun Batahan Mandailing Natal. 3) Partial analysis of the effect of work assignments on employees of PT Palmaris Raya Kebun Batahan Mandailing Natal. 4) Application of strict professional discipline to the employment situation of employees of PT Palmaris Raya Kebun Batahan Mandailing Natal. 5) The influence of leadership style, supervision, and work discipline so far on the performance of PT Palmaris Raya Kebun Batahan Mandailing Natal employees. 325 people are the sample population in this study, and 76 people are taken from rumpus slovin using incidental sampling technique as a sample. The results of the research and hypothesis testing are as follows: 1) Responsibility is the most important indicator of a strong leadership relationship, followed by integration and accuracy in supervision, adherence to standard operating procedures for work, and quality in working alone. 2) Partial leadership is positive and significant to the employment of employees of PT Palmaris Raya Kebun Batahan Mandailing Natal. 3) Partial positive and significant suggestions about the staffing of employees of PT Palmaris Raya Kebun Batahan Mandailing Natal. 4) Professional discipline has a positive and significant effect on the employment status of employees of PT Palmaris Raya Kebun Batahan Mandailing Natal. 5) Leadership, supervision, and professional discipline are all simultaneously significant to the working conditions of employees of PT Palmaris Raya Kebun Batahan Mandailing Natal.